Influence of motivation on employee performance with compensation as a moderating variable at PT Putikayo International using the Structural Equation Modeling (SEM) method - I Gede Marendra; I Made Aryata (Jurnal Mantik, 2023)
PT Putikayo International is a cosmetics manufacturer that has been established since December 13 2010 where employee performance is only 89.85%. Therefore, it is necessary to carry out an analysis to determine the factors that influence employee performance. The aim of the research conducted was to find out whether compensation strengthens the influence of motivation on the performance of PT Putikayo Internasional employees. The research method used was Structural Equation Modeling (SEM) by looking at the resulting p-value. The results of the research carried out show that: 1) Compensation has no effect on employee performance with a p-value of 0.232; 2) Motivation influences employee performance with a p-value of 0.000 and 3) Compensation strengthens the influence of motivation on employee performance at PT Putikayo Internasional with a p value of 0.002. From the results of this research it can be concluded that providing compensation will strengthen employee motivation at work so that employee performance will increase.